2014
DOI: 10.1007/s10578-014-0482-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Child PTSD Symptom Scale in Spanish and English

Abstract: Background Given the consistent growth of the Latino population in the United States, there is a critical need for validated Spanish measures to assess posttraumatic stress disorder (PTSD) symptoms in children. The current study examines the psychometric properties of the Child PTSD Symptom Scale (CPSS). Methods We examined 259 children (8 to 17 years) who had experienced a recent traumatic event. Study measures were completed in Spanish (n=106; boys = 58, girls = 48) or in English (n=153; boys = 96, girls =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…The 17-item Spanish translation of the Child PTSD Symptom Scale (CPSS) [17], corresponding to the DSM-IV criteria, was used to produce a PTSD symptom score by summing all items, with high internal consistency reliability (α = 0.94). The psychometrics for the Spanish version of the CPSS were recently examined and found to have good internal consistency reliability (α = 0.88) and moderate construct validity [25]. …”
Section: Methodsmentioning
confidence: 99%
“…The 17-item Spanish translation of the Child PTSD Symptom Scale (CPSS) [17], corresponding to the DSM-IV criteria, was used to produce a PTSD symptom score by summing all items, with high internal consistency reliability (α = 0.94). The psychometrics for the Spanish version of the CPSS were recently examined and found to have good internal consistency reliability (α = 0.88) and moderate construct validity [25]. …”
Section: Methodsmentioning
confidence: 99%
“…A total PTSD score (range = 0–51) is calculated by summing all items, whereas re-experiencing (range = 0–15), avoidance (range = 0–21), and hyperarousal (range = 0–15) severity scores are calculated by summing relevant subscale items. The CPSS has proved good psychometric properties [ 54 , 55 , 56 , 57 ]. With the current sample, coefficients alpha were 0.75, 0.72, and 0.71 for re-experiencing, avoidance, and hyperarousal, respectively, and .88 for the total scale.…”
Section: Methodsmentioning
confidence: 99%
“…The CPSS subscales and total scale exhibited excellent internal reliability in our sample, similar to what has been found in other studies from LMIC (Kohrt et al, 2011; Tol et al, 2008, 2013; Ventevogel, Komproe, Jordans, Feo, & De Jong, 2014). Studies of the factor structure of this scale are mixed as to whether it is best characterized as a measure of one general PTSD construct or of three distinct symptom clusters (Meyer, Gold, Beas, Young, & Kassam-Adams, 2014; Stewart, Ebesutani, Drescher, & Young, 2015). In our study, both models showed adequate fit, though the three-factor model performed marginally better.…”
Section: Discussionmentioning
confidence: 99%